2018
DOI: 10.1002/mc.22850
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial to mesenchymal transition is involved in ethanol promoted hepatocellular carcinoma cells metastasis and stemness

Abstract: Hepatocellular Carcinoma (HCC) is a malignant tumor with high rate of relapse and metastasis. Ethanol is a well‐known risk factor for HCC; it promotes the progression and aggressiveness of HCC. However, the underlying mechanism remains unclear. In clinic studies, we showed that alcohol consumption is positively correlated with TNM stage and vessel invasion; HCC patients with chronic drinking history had faster progression rate and poorer prognosis compared to non‐drinkers. In experimental models, ethanol expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…The pathological features of EMT include loss of cell-to-cell adhesion and cell polarity by epithelioid cells, which then transform into mesenchymal cells with increased proliferative, migratory, and invasive capacities. 23,24 In our study, western blot analysis revealed that overexpression of circRNA_100395 increased the expression of the epithelial marker, E-cadherin, and suppressed the mesenchymal proteins, N-cadherin, vimentin, and Slug, in PC3 and DU145 cells. Emerging studies have indicated that cell growth and metastasis are affected by EMT.…”
Section: Discussionsupporting
confidence: 50%
“…The pathological features of EMT include loss of cell-to-cell adhesion and cell polarity by epithelioid cells, which then transform into mesenchymal cells with increased proliferative, migratory, and invasive capacities. 23,24 In our study, western blot analysis revealed that overexpression of circRNA_100395 increased the expression of the epithelial marker, E-cadherin, and suppressed the mesenchymal proteins, N-cadherin, vimentin, and Slug, in PC3 and DU145 cells. Emerging studies have indicated that cell growth and metastasis are affected by EMT.…”
Section: Discussionsupporting
confidence: 50%
“…The transition of cells from epithelial to mesenchymal phenotype (EMT) enhances the migratory and invasive properties of cancerous cells and cause metastasis of malignant tumor 19,20. MiRNAs are reported to regulate EMT mediated metastasis 21–23.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial-mesenchymal transition (EMT) is a biological process in which epithelioid cells lose cell-to-cell adhesion and cell polarity and then transform into mesenchymal cells with increased migratory and invasive abilities [23,24]. A growing number of studies indicate that circRNA inhibits cell metastasis via suppression of the EMT pathway [25,26].…”
Section: Discussionmentioning
confidence: 99%